Pemberdayaan Petani Pemakai Air (P3A) Dalam Pengelolaan Irigasi di Daerah Irigasi Baumata Kabupaten Kupang - Nurwiana, Ida; Abdurrahman, Mustafa (JGEN : Jurnal Pengabdian Kepada Masyarakat, 2024)
Water as a renewable natural resource, has the most fundamental and essential role in the sustainability of human life in supporting various activities, such as: agriculture, clean water for households, industry, aquaculture, tourism, mining and electric power. One use of water is for agriculture as irrigation water. Irrigation water managed by the Dua Serangkai P3A Group in the Baumata Irrigation Area is experiencing operational and maintenance (OM) obstacles due to limited water and limited OM soft skill capabilities of tertiary irrigation canals. The aim of this service is that irrigation water can be managed well through empowering P3A, improving the soft skills of tertiary irrigation canals OM, drafting a tertiary irrigation canals OM manual, agreeing on a water management system and assisting in drafting P3A AD/ART. Management of irrigation water in the Baumata Irrigation Area through P3A empowerment has experienced an increase in knowledge of soft skills for tertiary irrigation canals OM, drafting a tertiary irrigation canals OM manual, agreed on a water distribution system from upstream to downstream by: rainy season planting rice, setting regulated water distribution schedules P3A according to each block, while in the dry season horticulture/mixed planting, daily water arrangements are regulated by the clan according to the agreed schedule as well as assistance in preparing P3A AD/ART.